2021
DOI: 10.3390/polym13040594
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Poly(Lactic Acid) Biocomposites under Controlled Composting Conditions and Freshwater Biotope

Abstract: The influence of additives such as natural-based plasticiser acetyl tributyl citrate (ATBC), CaCO3 and lignin-coated cellulose nanocrystals (L-CNC) on the biodegradation of polylactic acid (PLA) biocomposites was studied by monitoring microbial metabolic activity through respirometry. Ternary biocomposites and control samples were processed by a twin-screw extruder equipped with a flat film die. Commonly available compost was used for the determination of the ultimate aerobic biodegradability of PLA biocomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…In our previous study [ 48 ], we reported the similar dependence of the influence of ATBC, L-CNC, and CaCO 3 additives on the biodegradation potential of PLA. The synergistic effect of ATBC/CaCO 3 on the biodegradation rate PLA has been observed.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…In our previous study [ 48 ], we reported the similar dependence of the influence of ATBC, L-CNC, and CaCO 3 additives on the biodegradation potential of PLA. The synergistic effect of ATBC/CaCO 3 on the biodegradation rate PLA has been observed.…”
Section: Resultssupporting
confidence: 60%
“…Based on the results, all material variants that accomplished the requirements of EN 13432 standard for packaging recoverable through composting can be stated. In our previous study [48], we reported the similar dependence of the influence of ATBC, L-CNC, and CaCO3 additives on the biodegradation potential of PLA. The synergistic effect of ATBC/CaCO3 on the biodegradation rate PLA has been observed.…”
Section: Determination Of Ultimate Aerobic Biodegradabilitysupporting
confidence: 64%
See 1 more Smart Citation
“…Temperature is the first important limiting parameter, since only above PLA glass transition temperature (55 °C) the increased flexibility of the chains facilitates the accessibility to chemical and biological degradation. [11] So, PLLA does not degrade at mesophilic temperatures (25 and 37 °C), while at 60 °C its degradation degree reaches 90 % within 120 days. [12] For this reason, PLA is not suitable for home composting degradation.…”
Section: Composting Versus Re/upcycling For Specific Biodegradable Polymers: State Of the Artmentioning
confidence: 91%
“…1 At present, mature biodegradable plastic films mainly include polylactic acid, 2 polycaprolactone 3 and biopolyesters, 4 but they generally have the shortcomings of long degradation cycles and incomplete degradation. 5,6…”
Section: Introductionmentioning
confidence: 99%